2013
DOI: 10.5812/jjm.7686
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hypervariable Region (HVR) of mecA Gene in Staphylococcus aureus Isolated From Nasal Carriers and Clinical Samples

Abstract: Background: Methicillin Resistant Staphylococcus aureus (MRSA) is a common major human pathogen that causes hospital-acquired infections. Characterization and typing of the staphylococcal cassette chromosome has led to a better understanding of MRSA infection cycle in hospital. The mecA-associated hypervariable region size classifies MRSA isolates that colonized in nasal carriers. Objectives: The aim of this study was to compare the genetic background of hypervariable region (HVR) of mecA gene in S. aureus iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Previous studies in Iran have reported a high rate of MRSA infections (9,23). The results of the current study showed an MRSA infection rate of 20.4% in the samples collected from different wards.…”
Section: Discussionsupporting
confidence: 55%
“…Previous studies in Iran have reported a high rate of MRSA infections (9,23). The results of the current study showed an MRSA infection rate of 20.4% in the samples collected from different wards.…”
Section: Discussionsupporting
confidence: 55%
“…In human medicine, S. aureus nasal carriage has been extensively studied in patients and healthy individuals ( 19 , 20 ). In Iran, resistance and nasal carriage of S. aureus in healthy children ( 21 ) and health care workers ( 22 ) have also been studied. The latter research also concluded that S. aureus could be transmitted from health care workers to hospitalized patients.…”
Section: Introductionmentioning
confidence: 99%